COVID-19: General aspects and impacts on the health of the elderly (Research, Society and Development, 2023)
COVID-19 is characterized by being a viral infection of the airways that mainly affects epithelial/alveolar and endothelial cells, resulting in the desquamation of pneumocytes, the presence of hyaline membrane, interstitial formation and inflammation with infiltration of lymphocytes, which can evolve with adverse outcomes serious diseases, such as pneumonia, disseminated intravascular coagulation (DIC) and multiple organ failure. The objective of the work is to elucidate the pathophysiology of COVID-19, discuss diagnostic methods, list the main symptoms and forms of treatment. Furthermore, address the impacts on the elderly population, as the highest death rates occur in this population. To this end, an integrative review of the literature, of a descriptive nature, was carried out. In relation to the diagnosis of COVID-19, it can be carried out using clinical, clinical-epidemiological, clinical-imaging and laboratory methods. Complications from COVID-19 mainly affect individuals who meet the risk factors: elderly, smokers, hypertensive, diabetic, obese and immunodeficient. Some studies indicated that almost half of deaths from COVID - 19 occurred among institutionalized elderly people and that more than 100 thousand elderly people were fatally affected in the country, in addition to an increase in morbidity and mortality in those who use ACE inhibitors or ARA-II and, in general, this population had the most frequent symptoms of fever, cough and dyspnea, but they are more fragile because they are more susceptible to infections, due to immunosenescence. Furthermore, there are several drugs being evaluated for the management of COVID, such as antivirals, antibodies, anti-inflammatory agents, immunomodulators, anticoagulants and antifibrinolytics.